Vessel wall enhancement of a ruptured intra-nidal aneurysm in a brain arteriovenous malformation. Issue 3 (June 2019) - Bhogal, Pervinder; Lansley, Joseph; Wong, Ken; Udani, Sundip D; Uff, Chris; Wadley, John; Kumar, Atul; Matouk, Charles C; Makalanda, Hegoda LD
Ruptured arteriovenous malformations are a frequently encountered pathology with significant associated morbidity and mortality. Identifying and securing the rupture point is mandatory; however, this can often be difficult. Black blood vessel wall magnetic resonance imaging is a promising technique for identifying ruptured saccular aneurysms and has been used in cases of multiple aneurysms. Here we describe a case of using this imaging technique to identify the rupture point in a ruptured arteriovenous malformation with histopathological correlation.